Case 3: Infusion-ing the information technology resources efficiently - Ku-Mahamud, Ku Ruhana; Ahmad, Faudziah; Abd Razak, Rafidah; Abd Ghani, Nor Farzana
The company is in the middle of structuring and organizing information technology (IT) resources between the four business arms of the company, aimed at solidifying its competitive footing and preparing itself for public listing. Dedicated to be a prime promoter of the knowledge hub with distinctive emphasis in the knowledge management system, In-Fusion Solutions Sdn. Bhd. (ISSB) is now making its mark in the local on-demand knowledge delivery landscape and plans to become a public listed company in the near future. With the growing list of clients ISSB foresees the need of becoming more eficient, thus a Chief Information Oficer (CIO) has been brought onboard to oversee IT resources eficiently in the company. Among the company's challenges are lack of powerful tools for managing product development data and too much dependency on the open source tools. On the other hand, other tools to support crucial business finctions of which are located at different locations and on different platforms, such as help-desk, customer relationship management,financial management, etc. also need to be enhanced and some need to be developed. The current inter-networking infrastructure also calls for the CIO and ISSB's management attention. IT resources such as hardware and sofhvare among employee and remote access solution many increase eficiency by permitting remote users to securely access information from anywhere at anytime and this needs to be addressed urgently. Greater network capacity provides greaterability for ISSB to handle business transactions. Each of the inter-networking components generates opportunities and issues that the ISSB management must understand and be able to effectively address. In a nutshell, these issues need to be resolved as soon as possible for the company to move forward to be public listed next year and to be able to keep up with fiture projects in the pipeline.